PENGARUH PIJAT BAYI TERHADAP PENINGKATAN PERKEMBANGAN MOTORIK KASAR PADA BAYI USIA 0-3 BULAN - Damai Yanti; Sofa Fatonah; Rina Maryani; Rini Mulyasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
Baby massage is a form of stimulus given by the midwife to stimulate the baby's gross motor development. Several internal and external factors can affect gross motor development in infants. This study uses a quantitative research design, which uses the one group pretest-posttest design method, namely one intervention group without a control group, with a total of 17 infants as respondents, after 4 massages in 1 month an assessment using KPSP was carried out. The results of the T-test showed an increase in the appropriate category, while in the decreasing category there was a decrease in the value of sig. 0.018 and <0.05, it can be concluded that Ha is accepted and Ho is rejected, so there is an effect of baby massage on the baby's gross motor development.